Experiences, attitudes and trust: an inquiry into elite athletes' perception of the whereabouts reporting system - Overbye, M.; Wagner, U. (International Journal of Sport Policy and Politics, 2013)
The duty of elite athletes to report whereabouts is a controversial and debated element of the World Anti-Doping Code. Though the obligation to provide whereabouts information has a real impact on athletes` daily lives, knowledge about athletes` perception of and trust in the system after the Code was revised in 2009 is still scarce. This study contributes to the discussion on the legitimacy and institutionalization of the whereabouts system by integrating the points of view of Danish elite athletes (with/without whereabouts obligations). In total, 645 athletes completed a web-based questionnaire about their perceptions of the whereabouts system. The results showed that elite athletes` perceptions were ambivalent: a majority of athletes seemed to accept the system as a necessity, a duty or a compliment to their sporting level. On the other hand, the system did, to a greater or lesser degree, interfere negatively in everyday life: three quarters of the athletes felt reporting whereabouts was too time-consuming; fear of a warning was a concern for more than half of the athletes; four in ten found their joy of being an elite athlete was reduced; and four in ten experienced the system as surveillance. Athletes` trust in the system was remarkably low when it came to questions concerning how it operated in other countries and its ability to catch doped athletes. A particular remarkable finding is that distrust seemed to increase once athletes had personal experience of reporting whereabouts. This must be considered a major challenge for future anti-doping policymaking.